The genera Isorineloricaria and Aphanotorulus (Siluriformes: Loricariidae) with description of a new species - Ray, C. Keith; Armbruster, Jonathan W. (Zootaxa, 2016)
We review the complex history of those species included in the Hypostomus emarginatus species complex and recognize them in Isorineloricaria and Aphanotorulus. Isorineloricaria consists of four valid species: I. acuarius n. sp., I. spinosissima, I. tenuicauda, and I. villarsi. Aphanotorulus consists of six valid species: A. ammophilus, A, emarginatus, A. gomesi, A. horridus, A. phrixosoma, and A. unicolor. Plecostomus annae and Hypostoma squalinum are placed in the synonymy of A. emarginatus; Plecostomus biseriatus, P. scopularius, and P. virescens are placed in the synonymy of A. horridus; Plecostomus winzi is placed in the synonymy of I. tenuicauda, and one new species, I. acuarius is described from the Apure River basin of Venezuela. Aphanotoroulus can be distinguished from Isorineloricaria by having caudal peduncles that do not become greatly lengthed with size and that are oval in cross section (vs. caudal peduncle proportions that get proportionately longer with size and that become round in cross-section), and by having small dark spots (less than half plate diameter) on a light tan background (vs. spots almost as large as lateral plates on a nearly white background.